Enhancing the Supply Chain of a Company in the Peruvian Food Sector through Digital Transformation - Cieza Miraval, Francisco Javier (2024)
The success of the supply chain is assessed through the efficiency and effectiveness of the innovative strategies that a company provides to its customers. Currently, companies face significant challenges in improving their service levels due to constant innovations in digitization. This study aimed to evaluate the impact of digitization and automation on the supply chain of a Peruvian fast-moving consumer goods company. Using a three-phase simulated design methodology with the involvement of relevant departments within the company, the goal was to analyze the impact of implementing new software to improve Fill Rate, a service level indicator used by the company. The main findings reveal a technical gap of 14.38%, and the objective of achieving 80% is expected to be met by the end of this year. Finally, this research serves as a starting point for further evaluation and analysis of the indicator's impact with the software in other areas. This will enable the investigation of new tools that are more aligned with the specific needs of each area to enhance its service level.